Ultrasound- and Microbubble-Assisted Gemcitabine Delivery to Pancreatic Cancer Cells - Tormod Bjånes; Spiros Kotopoulis; Elisa Thodesen Murvold; Tina Kamčeva; Bjørn Tore Gjertsen; Odd Helge Gilja; Jan Schjøtt; Bettina Riedel; Emmet McCormack (MDPI AG, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is a major cause of cancer death worldwide. Poor drug delivery to tumours is thought to limit chemotherapeutic treatment efficacy. Sonoporation combines ultrasound (US) and microbubbles to increase the permeability of cell membranes. We assessed gemcitabine uptake combined with sonoporation in vitro in three PDAC cell lines (BxPC-3, MIA PaCa-2 and PANC-1). Cells were cultured in hypoxic bioreactors, while gemcitabine incubation ± sonoporation was conducted in cells with operational or inhibited nucleoside membrane transporters. Intracellular active metabolite (dFdCTP), extracellular gemcitabine, and inactive metabolite (dFdU) concentrations were measured with liquid chromatography tandem mass spectrometry. Sonoporation with increasing US intensities resulted in decreasing extracellular gemcitabine concentrations in all three cell lines with inhibited membrane transporters. In cells with inhibited membrane transporters, without sonoporation, dFdCTP concentrations were reduced down to 10% of baseline. Sonoporation partially restored gemcitabine uptake in these cells, as indicated by a moderate increase in dFdCTP concentrations (up to 37% of baseline) in MIA PaCa-2 and PANC-1. In BxPC-3, gemcitabine was effectively inactivated to dFdU, which might represent a protective mechanism against dFdCTP accumulation in these cells. Intracellular dFdCTP concentrations did not change significantly following sonoporation in any of the cell lines with operational membrane transporters, indicating that the gemcitabine activation pathway may have been saturated with the drug. Sonoporation allowed a moderate increase in gemcitabine transmembrane uptake in all three cell lines, but pre-existing nucleoside transporters were the major determinants of gemcitabine uptake and retention.